A Site-Specific Fertilizer Recommendation Based on the Phosphorus and Potassium Status in Mempawah District, West Kalimantan - Muhammad Hatta (JOURNAL OF TROPICAL SOILS, 2020)
The recommendations of Phosphorus (P) and Potassium (K) fertilization for rice are still not site-specific yet due to a lack of required soil data information.  The P and K status of the paddy fields that provide information on the low, medium, and high P and K nutrient status are very useful for determining recommended the site-specific fertilizer in the the district area. The purpose of the research was to determine the site-specific fertilizer recommendation for paddy field based on their P and K status. This research was based on the field survey and the soil analysis in the laboratory. The soil samples were taken using a grid system, and the P and K levels were assessed by using a 25% HCl extraction. Soil samples were taken in a composite manner on all paddy fields in which their status have been identified. The composite soil samples were determined from 10 - 15 individual samples (sub-samples) with a sampling distance of each sub-sample of 25-50 m in the field.  The soil samples were taken in the overlay with a depth of 0-20 cm. Taking sub-samples were done by a diagonal or a zigzag method according to the conditions of paddy fields. The results of the study presented that the nutrient status of P and K and the fertilizer recommendations in paddy fields for rice plants located in 9 sub-districts in Mempawah Dsitrict had shown that nutrient status of P, on average, were from moderate to high levels, meanwhile, the nutrient status of K was from low to high levels. Recommendations for fertilizing rice fields in several sub-districts in Mempawah Regency are mostly 150 kg NPK (15:15:15) ha-1, 200 kg Urea ha-1 and 25 kg KCl ha-1.